Introgression of natural genetic variations affecting trichome development and terpenes biosynthesis to obtain insect-resistant tomatoes - Freitas, Rodrigo Therezan de (2019)
To deal with insect pests the tomato wild relatives produce a variety of defensive compounds in their glandular trichomes type-VI. By contrast, although cultivated tomatoes (Solanum lycopersicum L.), also display type-VI trichomes, the gland in cultivated tomato is much smaller containing mainly monoterpenes and low levels of cytosolic-derived sesquiterpenes, which have no apparent effect against insect pests. In the present work, we carried out crosses between the wild species S. habrochaites and the tomato cultivar Micro-Tom (MT) in order to create introgression lines (ILs). We successfully transferred the plastid-derived sesquiterpene pathway from S. habrochaites to type-VI trichomes of the cultivated tomato (cv. Micro-Tom). The trichomes of the introgressed line named MT-Sesquiterpene synthase 2 (MT-Sst2) showed even higher concentration of α-santalene, β-bergamotene, and α-bergamotene compared to the wild species type-VI glandular trichomes. Surprisingly, the presence of high amounts of plastid-derived sesquiterpenes was not sufficient to confer resistance to specific tomato pests in MT-Sst2. The sesquiterpene profile of MT-Sst2 and LA1777 unveils sesquiterpene-derived compounds only found in the wild species, which point for additional steps necessary to obtain insect-resistant tomatoes. This work paves the way for both the understanding of the morphology and functionality of type-VI trichomes and for breeding insect resistant tomatoes.